The effect of submaximal exercise preceded by single whole-body cryotherapy on the markers of oxidative stress and inflammation in blood of volleyball players - Mila-Kierzenkowska, C.; Jurecka, A.; Wozniak, A.; Szpinda, M.; Augustynska, B.; Wozniak, B. (Oxidative Medicine and Cellular Longevity, 2013)
The aim of the study was to determine the effect of single whole-body cryotherapy (WBC) session applied prior to submaximal exercise on the activity of antioxidant enzymes, the concentration of lipid peroxidation products, total oxidative status, and the level of cytokines in blood of volleyball players. The study group consisted of 18 male professional volleyball players, who were subjected to extremely cold air ( ) prior to exercise performed on cycloergometer. Blood samples were taken five times: before WBC, after WBC procedure, after exercise preceded by cryotherapy (WBC exercise), and before and after exercise without WBC (control exercise). The activity of catalase statistically significantly increased after control exercise. Moreover, the activity of catalase and superoxide dismutase was lower after WBC exercise than after control exercise ( ). After WBC exercise, the level of IL-6 and IL-1 was also lower ( ) than after control exercise. The obtained results may suggest that cryotherapy prior to exercise may have some antioxidant and anti-inflammatory properties. The relations between the level of studied oxidative stress and inflammatory markers may testify to the contribution of reactive oxygen species in cytokines release into the blood system in response to exercise and WBC.